2001
DOI: 10.1152/ajpendo.2001.281.5.e908
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in the feeding-induced activation of the insulin-signaling pathway in neonatal pigs

Abstract: In neonatal animals, feeding stimulates skeletal muscle protein synthesis, a response that declines with development. Both the magnitude of the feeding response and its developmental decline can be reproduced by insulin infusion, suggesting that an altered responsiveness to insulin is a primary determinant of the developmental decline in the stimulation of protein synthesis by feeding. In this study, 7- and 26-day-old pigs were either fasted overnight or fed porcine milk after an overnight fast. We examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
77
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 49 publications
9
77
2
Order By: Relevance
“…The PTP1B association with IR in muscle, but not liver, was lower in 7-compared with 26-day-old pigs (* P Ͻ 0.05). high insulin sensitivity of protein synthesis in skeletal muscle of 7-compared with 26-day-old pigs (14,37,46). Importantly, no developmental change in PTP1B activation in liver was detected, which is consistent with the previously reported lack of developmental change in insulin sensitivity in the liver (14,37).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The PTP1B association with IR in muscle, but not liver, was lower in 7-compared with 26-day-old pigs (* P Ͻ 0.05). high insulin sensitivity of protein synthesis in skeletal muscle of 7-compared with 26-day-old pigs (14,37,46). Importantly, no developmental change in PTP1B activation in liver was detected, which is consistent with the previously reported lack of developmental change in insulin sensitivity in the liver (14,37).…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies from our laboratory have shown an enhanced activation of the insulin-signaling pathway leading to translation initiation in skeletal muscle of the neonatal pig after food consumption (16,26,37). This feeding-induced activation of the IR, IRS-I, PI 3-kinase, and protein kinase B decreases with development in parallel with the developmental decline in the feeding-induced activation of translation initiation factors that regulate the binding of mRNA to 43S ribosomal complex.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations